2002
DOI: 10.1002/jcc.10089
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical calculation of vibrational spectra of large molecules—Raman and IR spectra for Buckminsterfullerene

Abstract: Abstract:In this work we demonstrate how different modern quantum chemical methods can be efficiently combined and applied for the calculation of the vibrational modes and spectra of large molecules. We are aiming at harmonic force fields, and infrared as well as Raman intensities within the double harmonic approximation, because consideration of higher order terms is only feasible for small molecules. In particular, density functional methods have evolved to a powerful quantum chemical tool for the determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
552
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 531 publications
(559 citation statements)
references
References 35 publications
5
552
0
2
Order By: Relevance
“…Auxiliary basis sets for the RI approximation of the two-electron integrals were taken from the TURBOMOLE library. 52 The SNF 53 program was used for numerical calculations of vibrational frequencies in harmonic approximation.…”
Section: A Computational Methodsmentioning
confidence: 99%
“…Auxiliary basis sets for the RI approximation of the two-electron integrals were taken from the TURBOMOLE library. 52 The SNF 53 program was used for numerical calculations of vibrational frequencies in harmonic approximation.…”
Section: A Computational Methodsmentioning
confidence: 99%
“…Thus, RM can simultaneously reveal the chemical composition and the structure of EPS at diverse biofilm formation stages (Janissen et al 2015). Specifically, RM has great advantage in detecting the analyte molecule with the symmetrical modes of molecular motion, which are not sensed by typical infra-red spectroscopy (Neugebauer et al 2002). Ivleva et al (2008) and Wagner et al (2009) used RM to monitor the chemical composition of different types of EPS during the biofilm formation process at selected Raman bands, which confirmed that RM can effectively supplement CLSM analysis.…”
Section: Raman Microscopymentioning
confidence: 73%
“…In order to compare our results with experimental data, zero-point vibrational energy (ZPVE) as well as the thermal contributions to the BSR enthalpy within the harmonic approximation were calculated using SNF [123]. This is in all cases based on the single conformation with minimum energy in accordance with the procedure of SCC.…”
Section: Methodsmentioning
confidence: 99%